2021
DOI: 10.3390/plants10071378
|View full text |Cite
|
Sign up to set email alerts
|

Mining of Leaf Rust Resistance Genes Content in Egyptian Bread Wheat Collection

Abstract: Wheat is a major nutritional cereal crop that has economic and strategic value worldwide. The sustainability of this extraordinary crop is facing critical challenges globally, particularly leaf rust disease, which causes endless problems for wheat farmers and countries and negatively affects humanity’s food security. Developing effective marker-assisted selection programs for leaf rust resistance in wheat mainly depends on the availability of deep mining of resistance genes within the germplasm collections. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 71 publications
(74 reference statements)
2
18
0
1
Order By: Relevance
“…This result was consistent with the results of the heat map and principal component (PCA) as analyses revealed that one-dimensional heatmap visualization of the interaction between the presence of rust races and wheat variety performance revealed grouping of the 18 wheat varieties. These results are in good agreement with those previously reported by [5,29,[47][48][49] The rate of rust disease increase (r-value) is one of the epidemiological parameters used for quantitative determination of partial resistance to stem and leaf rusts under field conditions. In this study, the performance revealed grouping of the 18 wheat genotypes into two distinct groups: the resistance group, as they displayed lower rates of disease increase with low r-value, and the susceptible group, the fast-rusting or the highly susceptible ones, when subjected to the same pathogen populations and under the same environmental field conditions as in the current study.…”
Section: Plos Onesupporting
confidence: 92%
See 2 more Smart Citations
“…This result was consistent with the results of the heat map and principal component (PCA) as analyses revealed that one-dimensional heatmap visualization of the interaction between the presence of rust races and wheat variety performance revealed grouping of the 18 wheat varieties. These results are in good agreement with those previously reported by [5,29,[47][48][49] The rate of rust disease increase (r-value) is one of the epidemiological parameters used for quantitative determination of partial resistance to stem and leaf rusts under field conditions. In this study, the performance revealed grouping of the 18 wheat genotypes into two distinct groups: the resistance group, as they displayed lower rates of disease increase with low r-value, and the susceptible group, the fast-rusting or the highly susceptible ones, when subjected to the same pathogen populations and under the same environmental field conditions as in the current study.…”
Section: Plos Onesupporting
confidence: 92%
“…On the other hand, based on the interaction between the presence of rust strains and wheat varieties, were developed. The heatmap was drawn with the aid of the ClustVis tool [28,29] and JavaScript script language [30].…”
Section: Statistical Analysis Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This result was confirmed by the results obtained at the adult plant stage. This result is consistent with [29,38]. On the other hand, the results of the leaf rust disease revealed that the susceptible reaction was…”
Section: Plos Onesupporting
confidence: 87%
“…В связи с этим, молекулярные маркеры являются основным инструментом для идентификации генов этой группы. В литературе содержится обширная информация о маркерах «возрастных» Lr-генов (Tomkowiak et al, 2019;Atia et al, 2021). Преимущественно это микросателлитные маркеры, которые подбирают при анализе определенных гибридных популяций, и многие из них имеют ограничение для массового скрининга.…”
Section: Introductionunclassified